2005
DOI: 10.1001/archopht.123.7.977
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Age, Sex, and Ethnicity With Myopia Progression and Axial Elongation in the Correction of Myopia Evaluation Trial

Abstract: To identify the baseline factors independently related to 3-year myopia progression and axial elongation in COMET.Methods: A total of 469 children were enrolled, randomly assigned to progressive addition lenses with aϩ2.00 diopter (D) addition or to single vision lenses and observed for 3 years. Eligible children were 6 to 11 years old, with spherical equivalent myopia of − 1.25 to−4.50 D, bilaterally. The primary and secondary outcomes, myopia progression by cycloplegic autorefraction and axial elongation by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
169
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(189 citation statements)
references
References 37 publications
18
169
1
1
Order By: Relevance
“…But, children who start Ortho-K younger have the largest reduction in axial length change vs. children wearing glasses. In this study, children who started Ortho-K at age 6-7 showed a mean increase of 0.57mm in axial length over a 3 year period compared to spectacle-wearing children in a study by Hyman et al [33], who showed 1.10 mm of axial length increase in three years. In contrast, the 10-11 yearold Ortho-K wearers in our study showed0.15 mm axial length increase versus 0.50 mm of axial length increase in the 11 yearold spectacle wearers.…”
Section: Age and Axial Length Changesmentioning
confidence: 46%
See 3 more Smart Citations
“…But, children who start Ortho-K younger have the largest reduction in axial length change vs. children wearing glasses. In this study, children who started Ortho-K at age 6-7 showed a mean increase of 0.57mm in axial length over a 3 year period compared to spectacle-wearing children in a study by Hyman et al [33], who showed 1.10 mm of axial length increase in three years. In contrast, the 10-11 yearold Ortho-K wearers in our study showed0.15 mm axial length increase versus 0.50 mm of axial length increase in the 11 yearold spectacle wearers.…”
Section: Age and Axial Length Changesmentioning
confidence: 46%
“…While these data provide a reference point, they do not provide normative data on axial length increase during childhood. This is due to numerous variables that may contribute to refractive and axial length changes including age of myopia onset [27,31], ethnicity [31][32][33][34][35][36], hours of near work [37], hours of time spent outdoors [38], mode of refractive correction [20,24,39] and parental history of myopia [40]. …”
Section: Axial Length Changes With Other Modes Of Correctionmentioning
confidence: 99%
See 2 more Smart Citations
“…An earlier age of onset is linked to faster progression, which in turn contributes to increased myopia severity and a higher risk of associated ocular pathologies. (Lin et al 1999, Mitchell et al 1999, Hyman et al 2005, Saw et al 2005, Flitcroft 2012 …”
Section: Prevalence Of Myopiamentioning
confidence: 99%